The Global Industrial Complex : Systems of Domination. - Best, Steven (Lexington Books, 2011)
The Global Industrial Complex: Systems of Domination, is a groundbreaking collection of essays by leading scholars from wide scholarly and activist backgrounds who examine the entangled array of contemporary industrial complexes - what the editors refer to as "the power complex"--That was first analyzed by C. Wright Mills in his 1956 classic work, The Power Elite.